The Effects of VPTI's Corporate Image and Service Quality on Satisfaction And Loyalty of The KSO SCISI Customers - Arie Satryo Wibowo; Heny K Suwarsinah; Lilik Noor Yuliati (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
This research aimed to measure the Customer Satisfaction Index (CSI) and Customer Loyalty Index (CLI), analyze the effects of service quality and corporate image on customer satisfaction, analyze the effects of service quality and corporate image on customer loyalty, analyze the effects of customer satisfaction on customer loyalty, analyze the indicators of service quadrants required to be improved by using the Cartesian diagram, and analyze the managerial implications for the company in an effort to improve customer satisfaction and customer loyalty. The method used in the research was surveys supported by questionnaires to the customers of importers of KSO SCISI. The determination of the respondents was carried out using the non-probability sampling, and the data were analyzed using CSI (Customer Satisfaction Index), CLI (Customer Loyalty Index), Structural Equation Modeling Linear Structural Relationship (SEM LISREL) and IPA (Importance Performance Analysis). The results of the research show that service quality had positive effects on customer satisfaction, the corporate image had positive effects on customer satisfaction, the service quality had positive and significant effects on customer loyalty, and the corporate image had positive effects on customer loyalty while customer satisfaction had no positive effects on loyalty. The Customer Satisfaction Index indicates that the customers were satisfied with the services provided by KSO SCISI, and the Customer Loyalty Index also indicates that the customers were loyal to the services provided by KSO SCISI.Keywords: KSO SCISI, VPTI, customer satisfaction, customer loyalty, SEM, lisrel